Neurological Considerations with COVID-19 Vaccinations - Boruah, Abhilasha P.; Heydari, Kimia; Wapniarski, Anne E.; Caldwell, Marissa; Thakur, Kiran T. (Seminars in Neurology, 2023)
The benefits of coronavirus disease 2019 (COVID-19) vaccination significantly outweigh its risks on a public health scale, and vaccination has been crucial in controlling the spread of SARS-CoV-2. Nonetheless, several reports of adverse events following vaccination have been published.To summarize reports to date and assess the extent and quality of evidence regarding possible serious adverse neurological events following COVID-19 vaccination, focusing on Food and Drug Administration (FDA)-approved vaccines in the United States (BNT162b2, mRNA-1273, and Ad26.COV2.S).A review of literature from five major electronic databases (PubMed, Medline, Embase, Cochrane Library, and Google Scholar) was conducted between December 1, 2020 and June 5, 2022. Articles included in the review were systematic reviews and meta-analysis, cohort studies, retrospective studies, case–control studies, case series, and reports. Editorials, letters, and animal studies were excluded, since these studies did not include quantitative data regarding adverse side effects of vaccination in human subjects.Of 149 total articles and 97 (65%) were case reports or case series. Three phase 3 trials initially conducted for BNT162b2, MRNA-1273, and Ad26.COV2.S were included in the analysis.The amount and quality of evidence for possible neurological adverse events in the context of FDA-approved COVID-19 vaccinations is overall low tier. The current body of evidence continues to suggest that COVID-19 vaccinations have a high neurological safety profile; however, the risks and benefits of vaccination must continue to be closely monitored.
Keywords: SARS-CoV-2; BNT162b2; mRNA-1273; Ad26.COV2.S